Lucas Algorithm for Medical Images Encryption and Transmission using Orthogonal Frequency Division Multiplexing for Medical Health Information Systems and its VLSI Realization - Ch, Gangadhar; Habibulla, Md (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Security of medical images is critical for transmission of medical images and relevant patient information through public health information systems networks. Image encryption is an important tool for protecting Medical images by converting them into unrecognisable formats for the transmission and receiption of medical images. This paper proposes an algorithm for medical image encryption using Lucas Algorithm, and a discrete wavelet transform based transmission and reception technique, which is known as orthogonal frequency division multiplexing(OFDM). This paper presents an implementation of Lucas Algorithm for image encryption and combines it with Discrete wavelet transform orthogonal frequency division multiplexing using Field Programmable Gate Array.